Comparison of premium life tables between existing model and integration model in family takaful - Puspa Liza, Ghazali; Mustafa, Mamat (2012)
Education plan takaful is one of the product plans in Family Takaful. The researchers strongly believe that the present premium life tables must be amended to make it a more reasonable plan for all categories of income earners. This new proposed model of premium life tables is called integration model. This research paper will compare the premium life tables of the existing model and the integration model for two types of Family Takaful model; the Mudharabah and Wakala. The focus will be on Surrender Value. Maturity Value and Death Coverage. The results of the research will show that the integration model is more inclusive than the existing model in premium life tables for clients to earn more money in the future.